The Role of Fiscal Decentralization in Sustainable Local Economic Development - Pandoyo (Yayasan Sinergi Kawula Muda, 2024)
This study examines the impact of fiscal decentralization on local economic development, emphasizing financial autonomy, transparency, and resource distribution equity. Using a comprehensive review of literature and empirical data, the research demonstrates that fiscal decentralization plays a crucial role in promoting economic growth when local governments have control over financial resources. The findings reveal that transparency in financial management enhances public trust and improves resource allocation efficiency, reducing corruption risks. Additionally, disparities in resource distribution remain a significant barrier to equitable economic development, necessitating policy interventions to ensure fair access to fiscal resources across regions. The study also highlights the influence of systemic factors, including governance structures and national fiscal policies, on the success of decentralization efforts. By comparing fiscal decentralization models from various countries, this study provides valuable insights into best practices and the contextual factors affecting policy effectiveness. The research concludes that a well-structured fiscal decentralization policy, complemented by strong transparency measures and equitable resource distribution, is essential for achieving sustainable local economic development. These findings offer critical implications for policymakers and future research on optimizing fiscal decentralization frameworks.